Repellent activity of herbal essential oils against Aedes aegypti (Linn.) and Culex quinquefasciatus (Say.) - Duangkamon Sritabutra; Mayura Soonwera (My University, 2013)
To determine the mosquito repellent activity of herbal essential oils against female Aedes aegypti and Culex quinquefasciatus. On a volunteer's forearm, 0.1 mL of each essential oil was applied to 3 cm×10 cm of exposed skin. The protection time was recorded for 3 min after every 30 min. Essential oil from clove oil in olive oil and in coconut oil gave the longest lasting period of 76.50 min and 96.00 min respectively against Aedes aegypti. The citronella grass oil in olive oil, citronella grass oil in coconut oil and lemongrass oil in coconut oil exhibited protection against Culex quinquefasciatus at 165.00, 105.00, and 112.50 min respectively. The results clearly indicated that clove, citronella and lemongrass oil were the most promising for repellency against mosquito species. These oils could be used to develop a new formulation to control mosquitoes.
Keywords: Culex quinquefasciatus; Coconut oil; Insect Pest Control Strategies